Development of the Kamar Sandi letter agenda information system application in the Pamsisinfosan Pusdatin Kemhan RI - Findi Zhafirah; M Azhar Prabukusumo; Aulia Khamas Heikhmakhtiar; Nadiza Lediwara; Angga Ferdian Mayuni (Jurnal Mandiri IT, 2026)
This study describes the development of a web based correspondence information application for managing incoming and outgoing letters in the Kamar Sandi unit (Pamsisinfosan Division, Pusdatin Kemhan RI), replacing a legacy Visual Basic desktop system with unreliable database access, single host limitation, no scheduled backups, and a non intuitive interface. This research employs the Rapid Application Development (RAD) method to facilitate iterative prototyping and rapid adaptation to operational requirements. Using a modular Laravel/Livewire + MySQL stack, the application centralizes letter metadata and master data (origin/destination, security degree, communication channel, cryptographic system) and provides automated agenda numbering, role-based access control (Admin, Pimpinan, Petugas), and a secure flow for classified letters via PIN validation and hashed identifiers. Supporting modules include a notification center, activity/audit logs, Excel/PDF export, and scheduled backup–restore with PIN gated downloads. Evaluation results indicate a significant increase in operational efficiency, evidenced by a ~60% reduction in mail recording time and a decrease in data retrieval duration from over 10 minutes to under 5 seconds, with a 100% success rate in eliminating agenda duplication errors. The application operationalizes these findings through granular authorization, input & CSRF validation, gated secret document access, indexed search with multi criteria filtering, and integrated backup–restore enhancing accessibility, retrieval efficiency, and auditability while lowering operational risk. Key contributions are: (1) translating migration pain points into an iterative implementation, (2) embedding security and preservation features at design time, and (3) presenting an evidence aligned functional model for government records management. Future enhancement can add retention policy automation and secure inter agency integration.